2023
DOI: 10.3389/fvets.2023.1227654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of classical music on growth performance, stress level, antioxidant index, immune function and meat quality in broilers at different stocking densities

Abstract: High-stocking density is one of the factors that can easily cause oxidative stress and inflammatory reaction of broilers. Currently, music therapy has been proposed to help animals relieve stress to some extent. However, it is still unclear whether classical music can alleviate stress in broilers at high stocking densities. Hence, this study aimed to investigate the effects of classical music on growth performance, stress level, antioxidant index, immune function and meat quality of broilers under different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
1
Order By: Relevance
“…The current study's findings are consistent with those reported by Ha et al (2021) in native Korean broiler chickens, as different stocking densities do not influence MDA activity. However, this differs from the results of a previous study by Gao et al (2023), which reported that different stocking densities influence MDA activity in broiler chickens; the higher the stocking density, the higher the MDA content. Food proteins have a more significant thermogenic effect than carbohydrates, and a high-protein diet lowers body temperature and mortality but does not improve broiler growth (Teyssier et al, 2022).…”
Section: Advances Incontrasting
confidence: 99%
“…The current study's findings are consistent with those reported by Ha et al (2021) in native Korean broiler chickens, as different stocking densities do not influence MDA activity. However, this differs from the results of a previous study by Gao et al (2023), which reported that different stocking densities influence MDA activity in broiler chickens; the higher the stocking density, the higher the MDA content. Food proteins have a more significant thermogenic effect than carbohydrates, and a high-protein diet lowers body temperature and mortality but does not improve broiler growth (Teyssier et al, 2022).…”
Section: Advances Incontrasting
confidence: 99%
“…In chicks, classical music was beneficial, presenting relatively low cortisol concentrations as a function of dB level, whereas exposure to noise reduced comforting and grooming behavior, impaired learning ability, and increased fear responses [96]. In broilers, classical music ameliorated the negative effects of high stocking densities [133]. In mice, white noise had detrimental effects on gut microbiota, antioxidant activity, and immunity, although music was potentially beneficial [90].…”
Section: Studies On Music In Non-human Animalsmentioning
confidence: 99%